TINJAUAN ATAS PENCATATAN BELANJA MODAL TERHADAP LAPORAN KEUANGAN DI BKD KOTA DEPOK - Nadia Putri Edyan (2021)
The importance of recording capital expenditures on financial statements at the Depok City BKD, namely as a form of the occurrence of a transaction activity in the development and maintenance of the needs of the fields. The recording of capital expenditures is recorded through two records, namely the BPP administration in the SIPKD application and financial reports in the form of SKPD financial reports. In the recording of capital expenditures, it provides knowledge about the grouping, and classification of capital expenditures on the SKPD Financial statements based on an accounting basis. The recording of capital expenditures has two mechanisms, namely by money supply/replacement/addition of money and directly. The accounting system used in the recording is the regional work unit system. Techniques in collecting data on the recording of capital expenditures on the financial statements, namely through learning, practice, and interviews with the accounting staff of the Depok City BKD. In recording capital expenditures, there are supporting documents, namely: letter of provision of funds, official memorandum of disbursement of funds, receipts, purchase invoices, general cash book of assistant treasurer of expenditures, book detailing the object of expenditure, warrant for seeking funds, letter of accountability. Recording is done when a shopping transaction occurs.